PENGELOLAAN 4 PILAR DIABETES MELLITUS UNTUK MENINGKATKAN EFIKASI DIRI - Ramadhani, Dwi Yuniar; Rukmini, Rukmini; Mamesah, Marline Merke (Community Development in Health Journal, 2024)
Introduction & Objectives: People with diabetes mellitus sometimes have trouble controlling blood glucose levels and have low self-efficacy. This can happen due to several factors ranging from lack of information, and complications of insufficient family support, causing a low quality of life. This community service aims to provide health education and identify self-efficacy and blood glucose levels. Method: The target of DM sufferers is 18 people. The implementation stage of the activity is the initial survey, health education about the 4 pillars of DM, data collection, and report preparation. Data were collected using a DMSES questionnaire and random blood sugar checks. Results: The majority of female respondents amounted to 14 respondents (77.8%), most of them suffered from DM for 1-6 months amounting to 12 respondents (66.7%), and poor and good self-efficacy each 9 respondents (50%), and 12 respondents (67%) could control. Discussion: Health education on managing the 4 pillars of DM is expected to increase knowledge and self-efficacy and control blood glucose.